QbD Assisted Method Development and Validation of Stability Indicating UV Spectrophotometric Method for Azelnidipine - Gavali¹, Kirankumar Jalindar; Maste¹, Meenaxi Maruti; Gawas¹, Nikhil Sunil; Suryawanshi², Shailendra Sanjay (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Azelnidipine, calcium channel blocker used in hypertension management, requires reliable analytical method to ensure its stability, quality, and regulatory compliance. Stability-indicating methods are essential for detecting and quantifying degradation products under stress conditions. Traditional spectrophotometric methods, however, often lack systematic approaches, robustness, and sensitivity. Integrating Quality by Design (QbD) principles into method development provides a structured approach to address these challenges, enhancing method performance and regulatory compliance. Materials and Methods: The UV spectrophotometric technique was developed using a 50:50 diluent ratio, and the λmax was found to be 258 nm. In the proposed study, QbD-assisted approach was employed to develop and validate stability-indicating spectrophotometric method for Azelnidipine. Risk assessment tools were used to identify Critical Quality Attributes (CQAs) and Critical Method Parameters (CMPs) that influence method performance. A Design of Experiments (DoE) approach was applied to systematically optimize method parameters. Stress degradation studies were conducted under acidic, basic, oxidative, thermal, and photolytic conditions, following International Council for Harmonization (ICH) guidelines. The method was validated for specificity, linearity, accuracy, precision, robustness, ruggedness, and solution stability. Results: The developed method demonstrated high accuracy, precision, and sensitivity in quantifying Azelnidipine and its degradation products. Stress testing showed significant degradation under acidic and oxidative conditions, with minimal degradation under basic conditions. The drug remained stable under thermal and photolytic stress. Validation results confirmed the method compliance with ICH Q2(R2), with a linear response observed in the 2-10 µg/mL concentration range and an excellent R² value of 0.9998 at 258 nm. Additionally, the area under the curve was measured at wavelength range of 242-276 nm. The QbD approach ensured a robust and reproducible method, minimizing variability and enhancing reliability for routine quality control and stability analysis. Conclusion: The QbD-assisted spectrophotometric method developed in this study provides cost-effective, robust, systematic, and regulatory-compliant solution for the stability analysis of Azelnidipine. The proposed study exemplifies how QbD approach can enhance analytical method development, ensuring greater reliability, improved pharmaceutical quality assurance, and compliance with modern regulatory standards.
Keywords: Azelnidipine; UV Spectrophotometry; Quality by Design; Forced Degradation; Central; Composite Design